Kesantunan Berbahasa Orang Tua dan Anak pada Youtube “Bolehkah Sekali Saja Kumenangis” - Amiruddin, Nurlina; Martutik, Martutik; Susanto, Gatut (Kajian Linguistik dan Sastra, 2025)
This study aims to describe the form of politeness in language by Prilly and her father in a video entitledSocial Experiment: “Can I cry just once?" Episode 1-Prilly Latuconsina on the Sinemaku Pictures YouTubechannel and the influence of the use of politeness maxims in language to create emotionalcommunication between parents and children. The politeness of language between parents and childrenis something that needs to be considered. The closeness factor often makes children forget the principlesof politeness when communicating with their parents. In analyzing the data, this study focuses oncompliance with the principles of politeness in language based on the theory developed by Leech. Thisresearch is a type of qualitative descriptive research. The data source in this study comes from the socialexperiment video "Can I cry just once?" Episode 1 on the Sinemaku Pictures YouTube channel in the formof speech uttered by Prilly and her father. The results of this study indicate that there are several maximsof politeness used by Prilly and her father, namely the maxim of humility, the maxim of appreciation,the maxim of generosity, the maxim of sympathy, the maxim of appropriateness, and the maxim ofwisdom. The maxims most often used are the maxim of humility and the maxim of appreciation, so thatthey can be a stimulus for the creation of emotional communication. This study can be a referencerelated to the importance of politeness applied in communication between children and parents.